The Role of Knowledge Management as Mediation on The Effect of Talent Management on Employee Performance - Ekhsan, Muhamad; Badrianto, Yuan (Universitas Pamulang, 2023)
This study aims to prove that knowledge management acts as a mediator between talent management and employee performance. The population of this research is the entire employee population of the firm services based in Bekasi, and there were 70 people who responded to the survey. The method for data collection that was used was a questionnaire submitted through a Google form, and the data were analyzed with smart PLS. The findings of this research reveal that talent management has an influence on employee performance and that knowledge management has the ability to act as a mediator between the influence of talent management and the influence it has on employee performance. The talent of management has become a determining factor in the success of businesses and the power of resources. Organizations are being put to the test to see how effectively they manage potential great people. Knowledge Management is able to develop expertise and motivation at work, which in turn pushes performance enhancement for individuals and companies. Every worker needs to have their own understanding of the company's knowledge because very bad knowledge is limiting and will keep the company from growing. The study thus still has drawbacks, one of which is that the data collecting instrument employs a questionnaire, which enables data to be acquired without being able to extract the information needed in a way that is comprehensive and in-depth.